Accelerating Hong Kong's reeducation: 'mainlandisation', securitisation and the 2020 National Security Law. Issue 2 (3rd April 2022) - Vickers, Edward; Morris, Paul
ABSTRACT: Whilst Hong Kong's return to Chinese sovereignty in 1997 has influenced education in various ways, major reforms perceived as promoting mainland control have been resisted. For two decades, Hong Kong's educational autonomy under the 'one country, two systems' formula was thus largely maintained. This changed radically with the response to the protests of 2019–2020, culminating in the introduction of a National Security Law. This has drastically constrained Hong Kong's civil society, enhanced central government control of education and accelerated efforts to reeducate Hongkongers as loyal PRC citizens. We trace how this transformation has been enacted and justified, and reflect on its consequences. We analyse the current situation through the lenses of 'internal colonialism' and securitisation, which have characterised governance of China's restive periphery under Xi Jinping. We argue that analytical perspectives in Comparative Education, relating to postcolonialism/decolonisation and globalisation, obstruct or distort understanding of Hong Kong's present predicament.